Disseminating child abuse clinical decision support among commercial electronic health records: Effects on clinical practice. Issue 2 (13th April 2023) - Feldstein, David A; Barata, Isabel; McGinn, Thomas; Heineman, Emily; Ross, Joshua; Kaplan, Dana; Bullaro, Francesca; Khan, Sundas; Kuehnel, Nicholas; Berger, Rachel P
Abstract: Objectives: The use of electronic health record (EHR)-embedded child abuse clinical decision support (CA-CDS) may help decrease morbidity from child maltreatment. We previously reported on the development of CA-CDS in Epic and Allscripts. The objective of this study was to implement CA-CDS into Epic and Allscripts and determine its effects on identification, evaluation, and reporting of suspected child maltreatment. Materials and Methods: After a preimplementation period, CA-CDS was implemented at University of Wisconsin (Epic) and Northwell Health (Allscripts). Providers were surveyed before the go-live and 4 months later. Outcomes included the proportion of children who triggered the CA-CDS system, had a positive Child Abuse Screen (CAS) and/or were reported to Child Protective Services (CPS). Results: At University of Wisconsin (UW), 3.5% of children in the implementation period triggered the system. The CAS was positive in 1.8% of children. The proportion of children reported to CPS increased from 0.6% to 0.9%. There was rapid uptake of the abuse order set. At Northwell Health (NW), 1.9% of children in the implementation period triggered the system. The CAS was positive in 1% of children. The child abuse order set was rarely used. Preimplementation, providers at both sites were similar in desire to have CA-CDS system and perception of CDS in general. After implementation, UW providers had a positive perception of the CA-CDS system, while NW providers had a negative perception. Discussion: CA-CDS was able to be implemented in 2 different EHRs with differing effects on clinical care and provider feedback. At UW, the site with higher uptake of the CA-CDS system, the proportion of children who triggered the system and the rate of positive CAS was similar to previous studies and there was an increase in the proportion of cases of suspected abuse identified as measured by reports to CPS. Our data demonstrate how local environment, end-users' opinions, and limitations in the EHR platform can impact the success of implementation. Conclusions: When disseminating CA-CDS into different hospital systems and different EHRs, it is critical to recognize how limitations in the functionality of the EHR can impact the success of implementation. The importance of collecting, interpreting, and responding to provider feedback is of critical importance particularly with CDS related to child maltreatment. Lay Summary: Child abuse is an important cause of injuries and death in children. The number of children who die every year in the US from child abuse is more than the number who die from flu, COVID, and respiratory syncytial virus added together. One way to decrease injuries and death from child abuse is for medical professionals to recognize it early, evaluate it properly and report to Child Protective Services when necessary, so that families can receive services and children can be protected from violent environments. Over the past 7 years, our team has been working to integrate changes into the electronic health record to help medical providers understand when they should and should not be concerned about child abuse. We have shown that the medical record can be used to help medical providers take better care of children who may be victims of child abuse. In this article, we demonstrate some of the barriers to expanding work we have done in one type of electronic medical record—called Cerner—to 2 other types of electronic medical records—called Epic and Allscripts. By understanding these challenges, we can improve our ability to disseminate our work more effectively and efficiently.